1997
DOI: 10.1021/ja971321m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraligand Electron Delocalization, Steric Tuning, and Excited-State Vibronic Coupling on the Photophysics of Aryl-Substituted Bipyridyl Complexes of Ru(II)

Abstract: The synthesis and photophysical characterization of a series of aryl-substituted 2,2‘-bipyridyl complexes of RuII are reported. The static and time-resolved emission properties of [Ru(dpb)3](PF6)2, where dpb is 4,4‘-diphenyl-2,2‘-bipyridine, have been examined and are contrasted with those of [Ru(dmb)3](PF6)2 (dmb = 4,4‘-dimethyl-2,2‘-bipyridine). It is shown through analysis of electrochemical data and detailed fitting of the emission spectrum that the unusually large radiative quantum yield for [Ru(dpb)3](PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
340
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 276 publications
(366 citation statements)
references
References 62 publications
25
340
0
1
Order By: Relevance
“…As was alluded to above, we have recently detailed the photophysics of [Ru(dpb) 3 ](PF 6 ) 2 and related compounds in the context of intraligand delocalization. 7 Synthetic manipulations of ligand structure provided compelling evidence that the photophysical properties of these compounds are dictated to a large extent by intraligand delocalization in the 3 MLCT excited state. The ligands, comprising what we refer to as the "dpb series", are illustrated below.…”
Section: Results Andmentioning
confidence: 99%
“…As was alluded to above, we have recently detailed the photophysics of [Ru(dpb) 3 ](PF 6 ) 2 and related compounds in the context of intraligand delocalization. 7 Synthetic manipulations of ligand structure provided compelling evidence that the photophysical properties of these compounds are dictated to a large extent by intraligand delocalization in the 3 MLCT excited state. The ligands, comprising what we refer to as the "dpb series", are illustrated below.…”
Section: Results Andmentioning
confidence: 99%
“…The details of this analysis are described elsewhere, 31,33,34 but essentially, the emission envelope is modeled as a sum of Gaussians spaced by the average vibrational mode coupled to the transition. E 0 then corresponds to the highest energy Gaussian and gives the relative vertical positions of the excited-and ground-state potential surfaces, i.e., the 3 MLCT/ 1 A 1 gap.…”
Section: Resultsmentioning
confidence: 99%
“…Instrumentation used for obtaining nanosecond time-resolved data has been described elsewhere. 31 Excited-state difference absorption spectra were obtained with constant laser excitation power (∼3 mJ at 480 nm) and pump-probe cross section, and were normalized for sample absorbance at the excitation wavelength for comparative purposes. The ∆OD values at the bleach minimum were very similar (∼0.11), and the spectra presented below are normalized to one at this minimum for comparison of energetic trends.…”
Section: Introductionmentioning
confidence: 99%
“…2 It was observed that the [Ru(dpb) 3 ] 2+ complex has a substantially smaller rate of nonradiative 3 MLCT f 1 A 1 relaxation following 1 MLCT r 1 A 1 absorption than what is seen for [Ru(dmb) 3 ] 2+ . Using a combination of synthetic and spectroscopic methods, 2 we demonstrated that the drop in nonradiative decay (k nr ) for [Ru-(dpb) 3 ] 2+ was linked to a decrease in excited-state geometric distortion relative to the ground state because of extensive conjugation between the bipyridyl fragment and the aryl substituents in the excited state. Theoretical studies of model ligand systems further supported the assignment of a fully conjugated reduced ligand in the excited state.…”
Section: Introductionmentioning
confidence: 99%